2021
DOI: 10.3389/fvets.2021.662102
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for Buck Kids in Dairy Goat Farming

Abstract: To start milk production, dairy goats need to give birth at least once. While most female kids are reared to become the next generation of dairy goats, only a small proportion of male kids (buck kids) are reared with reproduction aims. The market for buck kid meat, especially within Northern European countries, is currently relatively small compared to the number of bucks born. Therefore, the purposes for buck kids are limited and a substantial proportion of buck kid meat is used for pet food. Due to the limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In dairy goat breeding, to obtain greater economic benefits, it is necessary to breed more female kids than males. The most direct method to achieve this is to separate the X- and Y-chromosome-bearing sperm prior to insemination [ 3 , 4 ]. Flow cytometry is currently the most effective and widely used sperm separation method [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In dairy goat breeding, to obtain greater economic benefits, it is necessary to breed more female kids than males. The most direct method to achieve this is to separate the X- and Y-chromosome-bearing sperm prior to insemination [ 3 , 4 ]. Flow cytometry is currently the most effective and widely used sperm separation method [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Goat’s milk is similar to human milk in terms of nutritional content and ease of digestion and is often the first choice for consumers [ 1 , 2 ]. In dairy goat breeding, male kids increase the feeding cost of the farm, and their value is lower than that of female kids; therefore, breeding more female kids can improve the economic benefits of a farm [ 3 , 4 ]. Previous studies have shown that the environmental pH can affect the motility and metabolism of rabbit sperm [ 5 ], hamster sperm [ 6 ], and human sperm [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Productivity, inherently linked to the purpose of goat farming, is a key consideration in business activities such as this [7,8]. Various factors influence productivity, notably the level of production manifested as weight gain and slaughter yields.…”
Section: Introductionmentioning
confidence: 99%
“…Saanen goats continue to be popular around the world because of their high volume of milk; research to characterise and select goats for higher production continues [1]. In the meantime, similar to other agricultural sectors specialized in female-derived products (dairy, eggs), practical and ethical issues arise as there are only limited purposes for surplus male offspring [3]. This leads to limited scientific data that exists for male dairy goat production and is probably similar to those identified in male dairy calves [4].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to limited scientific data that exists for male dairy goat production and is probably similar to those identified in male dairy calves [4]. In the Netherlands, virtually all surplus male goats are fattened for either pet food or human consumption [3].…”
Section: Introductionmentioning
confidence: 99%